Etno cognitive properties range toponyms of Hindi and toponymy - Елдекенова, Ә. Б.; Кокеева, Д. М. (Journal of Oriental Studies, 2018)
The anthropocentric position as one of the forms of Indian linguistic research conducted in the regional toponymy review of the system to a specific area – in the names of certain ethno-cultural regions, is the study of the relationship of spiritual history. Regional toponymic materials, show the distribution patterns inherent in all-Indian toponymy revealing linguistic history, ethnocultural, ethnoсognitive stories that are unique to this region. The article discusses lingvohistorical, ethnocultural, ethnoсognitive patterns characteristic of Indian toponymy.